2020
DOI: 10.1093/jamia/ocaa298
|View full text |Cite
|
Sign up to set email alerts
|

Developing a standardized protocol for computational sentiment analysis research using health-related social media data

Abstract: Objective Sentiment analysis is a popular tool for analyzing health-related social media content. However, existing studies exhibit numerous methodological issues and inconsistencies with respect to research design and results reporting, which could lead to biased data, imprecise or incorrect conclusions, or incomparable results across studies. This article reports a systematic analysis of the literature with respect to such issues. The objective was to develop a standardized protocol for imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…To classify public opinions toward mask wearing, we first applied the sentiment analysis approach which has been commonly used in the literature to study attitudes expressed in social media data. 30 We tested four off-the-shelf sentiment analysis tools that have been most commonly used: Valence Aware Dictionary for sEntiment Reasoning (VADER), 31 TextBlob, 32 Stanford Natural Language Processing (NLP), 33 and Linguistic Inquiry and Word Count (LIWC). 30,34,35 We manually annotated the sentiment of 500 random tweets and compared the results to the outputs of these tools.…”
Section: Rq1a: Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…To classify public opinions toward mask wearing, we first applied the sentiment analysis approach which has been commonly used in the literature to study attitudes expressed in social media data. 30 We tested four off-the-shelf sentiment analysis tools that have been most commonly used: Valence Aware Dictionary for sEntiment Reasoning (VADER), 31 TextBlob, 32 Stanford Natural Language Processing (NLP), 33 and Linguistic Inquiry and Word Count (LIWC). 30,34,35 We manually annotated the sentiment of 500 random tweets and compared the results to the outputs of these tools.…”
Section: Rq1a: Attitudementioning
confidence: 99%
“…30 We tested four off-the-shelf sentiment analysis tools that have been most commonly used: Valence Aware Dictionary for sEntiment Reasoning (VADER), 31 TextBlob, 32 Stanford Natural Language Processing (NLP), 33 and Linguistic Inquiry and Word Count (LIWC). 30,34,35 We manually annotated the sentiment of 500 random tweets and compared the results to the outputs of these tools. We found that none of these off-the-shelf tools were able to produce accurate attitude classifications, at least not in our study context.…”
Section: Rq1a: Attitudementioning
confidence: 99%
“…6, there has been a proportional increase in both interest and research efforts to process and interpret the sentiments and trends that are present in social media data. This substantial increase in research efforts has been identified to have a detrimental effect on the consistency of experimental designs, processing of data sets, and incomparability and/or misinterpretation of results [202]. To this end, the work of Hu et al [202] presents a standardized methodology for the structuring and reporting of future works in the field of SA, which could contribute significantly to the comparability of the results of individual works in this field.…”
Section: Current Challenges and Most Relevant Resultsmentioning
confidence: 99%
“…The references studied in Section III were obtained by searching in different scientific search engines such as Scopus, Science Direct, IEEE Xplore, and Google Scholar, for the following keywords: Sentiment Analysis, Text Classification, Social Media, Social Networks, Health, Twitter, Facebook, Instagram, epidemic, pandemic, COVID-19, SARS-Cov-19, Influenza, Virus, Vaccine, Vaccination, Affliction, Mental Health, Mental Illness, Mental Disorder Psychiatric, Suicide, Depression, Public Sentiment, Discourse, and Public Health. These keywords were selected through a search of the most relevant literature on the subject of study of this work, following a literature search methodology based on the one presented in [202]. Upon obtaining a complete reference list, we proceeded to filter the literature based on a series of parameters.…”
Section: A Scopementioning
confidence: 99%
“…Social media generates a large amount of review data on the Internet that varies among topics, 𝑒.𝑔., online goods [34], government policies [25], and health care [16]. To facilitate the decisionmaking process, many opinion summarization techniques have been proposed to filter valuable opinions out of the massive review data [1,2,6,7,9,18,24,41,42,44].…”
Section: Introductionmentioning
confidence: 99%